2013
DOI: 10.1016/j.bbr.2012.10.055
|View full text |Cite
|
Sign up to set email alerts
|

MC4-R signaling within the nucleus accumbens shell, but not the lateral hypothalamus, modulates ethanol palatability in rats

Abstract: The Melanocortin (MC) system is one of the crucial neuropeptidergic systems that modulate energy balance. The roles of endogenous MC and MC-4 receptor (MC4-R) signaling within the hypothalamus in the control of homeostatic aspects of feeding are well established. Additional evidence points to a key role for the central MC system in ethanol consumption. Recently, we have shown that nucleus accumbens (NAc), but not lateral hypothalamic (LH), infusion of a selective MC4-R agonist decreases ethanol consumption. Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…or CeA infusion of the MC3/MC4R agonist MTII has been shown to reduce alcohol consumption in mice (Navarro et al, 2003; 2005), alcohol-preferring AA rats (Ploj et al, 2002) and P rats (York et al, 2011). Additionally, administration of a selective MC4R antagonist into the nucleus accumbens reduces voluntary ethanol consumption (Lerma-Cabrera et al, 2012) and ethanol palatability (Lerma-Cabera et al, 2013). Similarly, in situ hybridization studies have shown increased ratios of POMC/AgRP mRNA in the Arc of alcohol-preferring AA rats (Lindblom et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…or CeA infusion of the MC3/MC4R agonist MTII has been shown to reduce alcohol consumption in mice (Navarro et al, 2003; 2005), alcohol-preferring AA rats (Ploj et al, 2002) and P rats (York et al, 2011). Additionally, administration of a selective MC4R antagonist into the nucleus accumbens reduces voluntary ethanol consumption (Lerma-Cabrera et al, 2012) and ethanol palatability (Lerma-Cabera et al, 2013). Similarly, in situ hybridization studies have shown increased ratios of POMC/AgRP mRNA in the Arc of alcohol-preferring AA rats (Lindblom et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, infusion of a selective MC4R agonist into the nucleus accumbens, but not into the lateral hypothalamus, reduces voluntary ethanol consumption, while infusion of the selective antagonist HS016 increases ethanol consumption without affecting caloric intake in adult Sprague-Dawley rats (Lerma-Cabrera et al, 2012). Moreover, stimulation of MC4R signaling in the accumbens shell region dramatically reduces ethanol palatability (Lerma-Cabrera et al, 2013), which suggests a key role for MC signaling in limbic regions in the hedonic responses to ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, an MC4R antagonist enhances this anxiolytic effect and reduces the anxiety induced by alcohol withdrawal (Kokare et al, 2006). Moreover, an MC4R agonist in the NAc reduces hedonic reactions to alcohol while increasing aversive ones (Lerma-Cabrera et al, 2013). Therefore MCs, like CRF, may enhance the aversive aspects of alcohol drinking while simultaneously reducing the rewarding aspects.…”
Section: Neuropeptides With a Negative Feedback Relationship To Almentioning
confidence: 99%
“…As mentioned in previous sections, alcohol consumption strongly reduces the expression of α-MSH in the limbic system and hypothalamus (Olney et al, 2014), whereas MC4R activation within the Nac suppress ethanol drinking (Navarro et al, 2011; Lerma-Cabrera et al, 2013b). In spite of this evidence, it is unknown whether alcohol addiction, in particular during the adolescence, occurs due to an imbalance in the inflammatory profile of glial cells caused by low signaling of the MC system.…”
Section: Neuroinflammation Oxidative Stress and Glia-to-neuron Miscmentioning
confidence: 70%
“…In agreement with these data, infusion of a selective MC4R agonist (cyclo (NH-CH2-CH2-CO-His- D -Phe-Arg-Trp-Glu)-NH2) at the NAc and VTA, but not into the lateral hypothalamus (LH), diminish voluntary alcohol consumption in rats (Lerma-Cabrera et al, 2012). Follow-up work has demonstrated that MC signaling within the NAc contributes to alcohol consumption by modulating the non-homeostatic aspects (palatability) of intake (Lerma-Cabrera et al, 2013b), which bring to light the key role of MCs in limbic regions implicated in the hedonic response to alcohol.…”
Section: Crosstalk Between Alcohol Consumption and Melanocortin Systemmentioning
confidence: 99%